2006
DOI: 10.5713/ajas.2006.1179
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D Supplementation to Peak-producing Hens Fed Diets Differing in Fat Source and Level on Laying Performance, Metabolic Profile, and Egg Quality

Abstract: This experiment was designed to examine the effects of supplemental vitamin D on laying performance, metabolic profile and egg quality of hens fed diets containing different fat sources and levels. Lohman strains (n = 480) were assigned to one of 10 diets: basal diet (BD), BD plus 2.5 and 5.0% sunflower oil (SO) or tallow (T) at vitamin D provided 1× and 3× of the current recommendation. The experiment lasted from week 30 to 44 of age. Each diet was tested in 12 replicate cages of 4 hens. Production, metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
8
0
3
Order By: Relevance
“…The mechanism whereby humate affects the FA composition of egg yolk is largely unknown. Concentrations of FA in animal fats are reported to be highly variable depending upon various factors such as animal age and diet 19. Alteration in FA composition of egg yolk could result from humate being of plant origin and relate to it being derived from plant matter decomposed by bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism whereby humate affects the FA composition of egg yolk is largely unknown. Concentrations of FA in animal fats are reported to be highly variable depending upon various factors such as animal age and diet 19. Alteration in FA composition of egg yolk could result from humate being of plant origin and relate to it being derived from plant matter decomposed by bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D has regulatory effects on calcium and phosphorus ANOVA Probabilities homeostasis by stimulating bone calcium mobilisation and inhibiting urinary calcium excretion when hens are calcium deficient. The mode of action is through molecular mechanisms involving bone cells and vitamin D binding proteins (Soares et al, 1995;Sugiyama and Kusuhara, 2001;Turgut et al, 2006). Heat stress decreases growth rate and bone mineralisation as well as concentrations of vitamins and minerals such as vitamins C, E, D and A, Ca, P and Zn in poultry (Sahin and Kucuk, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…n-3= omega-3 fatty acid, n-6= omega-6 fatty acid, SFA= Saturated fatty acid, MUFA= Monounsaturated fatty acids; PUFA= (tallow, sunflower, fish and flaxseed oil) fed to broilers (Newman et al,3002) layers (Grobas et al, 2001) showed no changes on performance parameters (FI, FCR and EP). However, Turgut et al (2006) reported that dietary fat sources affected laying performance.…”
Section: Resultsmentioning
confidence: 99%
“…None of the inner and other egg quality parameters were influenced by dietary treatments (P>0.05). Others have also shown that dietary fat sources had no significant effect on egg quality parameters (Baucells et al, 2000;Grobas et al, 2001;Turgut et al, 2006).…”
Section: Resultsmentioning
confidence: 99%